Influence of boundary conditions in FEM model on structural behaviour of thin-walled steel beams strengthened by CFRP tapes - Rzeszut, Katarzyna; Szewczak, Ilona; Rozylo, Patryk (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
The main aim of the study is verification and validation of FEM numerical model of beams made of thin-walled steel profiles retrofitted by CFRP tapes Sika CarboDur S. Validation is are carried out based on own laboratory tests conducted on “Blachy Pruszyński” S-type beams. The CFRP tape are bonded to the beam at compressed or tensioned flange. The most important part of this study is focused on investigation of boundary conditions influence in FEM model developed in Abaqus program. Moreover the numerical models are also tested in terms of different mesh density and types of finite elements. Numerical analyses are carried out using Newton-Raphson iterative method to solve non-linear equilibrium equation. In the paper special attention is paid to the evaluation of the possibility to increase the load capacity of the beams by appropriate localisation of CFRP tape.